Employee Performance at the Jakarta Port Hospital as Seen By the Management Information System, Training, and Organizational Culture - Indriani, Salsabila; Apriani, Ari (Management Department Universitas Islam Negeri Sumatera Utara, 2023)
Nowadays, having a Management Information System (MIS) for a hospital is a very important thing to develop. This is due to the increasing complexity of the problems that exist in patient medical records and other administrative records related to the provision of hospital services that are reported to the relevant hospitals. This study aims to identify the combined and partial effects of management information systems, training, and organizational culture on employee performance and to ascertain which has a greater influence between direct effects (management information systems, training, and a combination of direct effects (management information systems, training, and organizational culture on employee performance) with indirect effects. The focus of this research is on management information systems, training, organizational culture, and employee performance, and was conducted at the Jakarta Port Hospital. A total of 502 people became the research population and only 83 employees became the research sample. The findings indicated that the management information system has a positive and significant impact on employee performance, it is stated that as the management information system improves, employee performance also does. Training has no impact on employee performance, it is stated that either high or low levels of training have no bearing on employee performance. Organizational culture has a positive and significant impact on employee performance, but only to a limited extent, it is stated that with improved organizational culture, employee performance will improve.Keywords: Employee Performance, Hospital, Management Information System, Organizational Culture, Training